KALIMAT TANYA DALAM FILM MAN OF STEEL KARYA DAVID S. GOYER - Poluan, Christania; Kodong, Fentje; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â This study entitled â€œThe Interrogative Sentence in the Film Man of Steel by David S. Goyerâ€, is aimed at identifying and analyzing the interrogative sentences found in the film. The data have been collected by focusing on the conversation among the characters in the film and analyzed based on Frank and Aarts and Aartsâ€™ concepts. Interrogative sentence is a sentence that contains subject and open with an auxiliary verb or a wh-word. Interrogative sentence which is open with an auxiliary verb is called yes/no question and another type ofÂ yes/no question that consist of statement appended to the question is called question tag. The result shows that there are three forms of interrogative sentence in English used in the film, those are yes/no question, tag question and interrogative-word question. Yes /No question can be answered by yes/no, tag question is a question that is added at the end of sentence, interrogative-word question beginsÂ with a question word such as : what, who, why, when, where, how, whom or which. In this film the characters Â use interrogative sentence without a question word but with rising intonation. According to its function in communication, interrogative sentence can be functioned as question and request. Â ——————————————-Keywords: Interrogative Sentence, Grammatical Analysis, Film Man of Steel by David S. Goyer